Categorical-ontological approach to the modeling and formation of the educational program "Computer science and digital intelligence" - Sahaida, P. I.; Kostikov, O. A.; Getman, I. A.; Сагайда, П. І.; Костіков, О. А.; Гетьман, А. А. (Sigma Software University, 2024)
The work is devoted to solving the problem of creating educational IT programs that meet both the requirements of the employer and the complex requirements of production. Improved traditional ontology modeling (which can be subjective) by applying category theory to add mathematical rigor and verifiability to ontological models. A model and algorithmic support was developed for the automation of the educational program formation for the master's degree in "Computer science and digital intelligence".
Keywords: categorical-ontological approach; modeling; educational program; computer science